Assessing Tagal community dependency on ecotourism-Based Tagal: A case study from The West Coast Division of Sabah, Malaysia - Shahirah Amirullah; Audrey Daning Tuzan; Assis Kamu; Affendy Hassan (Universiti Malaysia Terengganu, 2024)
The present study investigates the dependency level demographic factors that affect the rural community on the ecotourism-based Tagal that has been widely applied throughout the West Coast division of Sabah. As the Department of Fisheries (DoF) Sabah indicated, fifteen Tagal involving ecotourism were selected around Sabah, and 400 respondents were picked using proportional random sampling. A standardised questionnaire was used to conduct in-depth interviews with household heads. The ratio of their monthly Tagal income to their total monthly income from other sources was calculated to calculate the household’s dependency. A descriptive statistical research revealed that 87.3% of Tagal community families depend little on ecotourism-based Tagal. The link between reliance and the socioeconomic characteristics of respondents was investigated using ordinal regression analysis. In conclusion, the data revealed that a considerable percentage of the population demonstrated a low reliance on ecotourism-based Tagal, indicating that it has not yet become a substantial source of revenue for the community. In addition, the study underlined the impact of gender and family size on the degree of dependency.